2015
DOI: 10.1017/ice.2015.247
|View full text |Cite
|
Sign up to set email alerts
|

A Large Outbreak of Hepatitis C Virus Infections in a Hemodialysis Clinic

Abstract: BACKGROUND In November and December 2012, 6 patients at a hemodialysis clinic were given a diagnosis of new hepatitis C virus (HCV) infection. OBJECTIVE To investigate the outbreak to identify risk factors for transmission. METHODS A case patient was defined as a patient who was HCV-antibody negative on clinic admission but subsequently was found to be HCV-antibody positive from January 1, 2008, through April 30, 2013. Patient charts were reviewed to identify and describe case patients. The hypervariable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 20 publications
(19 reference statements)
1
47
0
1
Order By: Relevance
“…2 A series of studies have confirmed that HCV transmission on HD reflects lack of adherence to these precautions. 3 In contrast to the prevention of hepatitis B transmission in this setting, dedicated dialysis machines for HCV-infected patients are not recommended. 4 The likelihood of HCV acquisition while on HD is increased in units with a higher background prevalence of HCV infection, so an infected HD patient also places others at risk.…”
Section: Hepatitis C Virus (Hcv) Infection Remains Commoner In Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A series of studies have confirmed that HCV transmission on HD reflects lack of adherence to these precautions. 3 In contrast to the prevention of hepatitis B transmission in this setting, dedicated dialysis machines for HCV-infected patients are not recommended. 4 The likelihood of HCV acquisition while on HD is increased in units with a higher background prevalence of HCV infection, so an infected HD patient also places others at risk.…”
Section: Hepatitis C Virus (Hcv) Infection Remains Commoner In Patientsmentioning
confidence: 99%
“…In the haemodialysis (HD) population, HCV infection in part reflects acquisition of infection within dialysis units where its transmission can be effectively prevented by meticulous attention to body fluid precautions . A series of studies have confirmed that HCV transmission on HD reflects lack of adherence to these precautions . In contrast to the prevention of hepatitis B transmission in this setting, dedicated dialysis machines for HCV‐infected patients are not recommended .…”
mentioning
confidence: 99%
“…Inadequately cleaned and disinfected dialysis stations, priming buckets, HD machines, effluent drain wall box, and other equipment have been implicated in transmission of pathogens in HD facilities (2,3). The CDC has specific recommendations and checklists for dialysis station disinfection, which should be performed only after the patient has left the HD unit.…”
Section: Infection Control Proceduresmentioning
confidence: 99%
“…In addition to bacterial infections, patients on HD are also susceptible to viral infections, including hepatitis B (HBV), hepatitis C (HCV), HIV, and influenza. Outbreaks of HCV infections in HD facilities, which continue to occur with disturbing frequency, have often been due to poor infection control practices (2). In September of 2016, the Centers for Disease Control and Prevention (CDC) launched the Making Dialysis Safer for Patients Coalition to foster collaboration among dialysis organizations, physicians, public health officials, and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Any case of new HCV infection in a patient undergoing hemodialysis is likely to be a healthcare‐associated infection and should be reported to public health authorities in a timely manner. A recent publication describes a dialysis facility where an outbreak of HCV continued for 5 years before being detected, highlighting the importance of HCV screening to identify these infections early and prevent further transmission . HCV transmission can be prevented when proper infection prevention and environmental disinfection practices are consistently followed.…”
Section: Introductionmentioning
confidence: 99%